Centralized vs. decentralized wage formation: The role of firms' production technology - Boris Hirsch; Christian Merkl; Steffen Mueller; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2014)
This paper is the first to show theoretically and empirically how firms' production technology affects the choice of their preferred wage formation regime. Our theoretical framework predicts, first, that the larger the total factor productivity of a firm, the more likely it is to opt for centralized wage formation where it can hide behind less productive firms. Second, the larger a firm's scale elasticity, the higher its incentive to choose centralized rather than decentralized wage setting due to labor cost and straitjacket effects. As firms in Germany are allowed to choose their wage formation regime, we test these two hypotheses with representative establishment data for West Germany. We find that establishments with centralized bargaining agreements indeed have economically and statistically significantly larger total factor productivities and scale elasticities than comparable establishments outside the centralized bargaining regime. – – Diese Studie zeigt erstmals theoretisch und empirisch, wie die Produktionstechnologie die betriebliche Wahl des Lohnfindungssystems beeinflusst. Unser theoretisches Modell erlaubt zwei Vorhersagen: Erstens, je höher die totale Faktorproduktivität einer Firma ist, desto wahrscheinlicher entscheidet sie sich für eine zentralisierte Lohnfindung auf Branchenebene, wo sie sich hinter weniger produktiven Firmen verstecken kann. Zweitens, je höher die Skalenelastizität einer Firma, desto höher ist aufgrund von Arbeitskosten- und Zwangsjacken-Effekten ihr Anreiz, eine zentralisierte statt einer dezentralisierten Lohnfindung zu wählen. Da Arbeitgeber in Deutschland das Lohnfindungsregime frei wählen können, überprüfen wir diese Hypothesen mit repräsentativen Betriebsdaten für Westdeutschland. Es zeigt sich, dass Betriebe mit zentralisierten (Branchen-)Tarifverträgen tatsächlich ökonomisch und statistisch signifikant höhere totale Faktorproduktivitäten und Skalenelastizitäten aufweisen als vergleichbare Betriebe mit dezentraler Lohfindung.
Keywords: J50; 330; collective bargaining; bargaining coverage; Germany